The construction of ‘So What?’ criminology: a realist analysis - Matthews, Roger A. (Crime, law and social change, 2010)
From a realist perspective there is a growing body of criminology that can be classified as ‘So What?’ criminology in that it involves a low level of theorisation, thin, inconsistent or vague concepts and categories, embodies a dubious methodology or has little or no policy relevance. The production of ‘So What?’ criminology is, of course, no accident but the outcome of a number of lines of force that have served to shape the nature of mainstream academic criminology in recent years. The aim of this article is to identify some of these lines of force and to assess their impact.